The Transformation of Political Culture in the Philippines After Marcos: A Critical Review - Noah Bennett; Gabriel Fernandez (JOCER: Journal of Civic Education Research, 2025)
This study aims to critically examine the transformation of political culture in the Philippines since the fall of the authoritarian regime of Ferdinand Marcos in 1986. The fall of Marcos, marked by the peaceful People Power Revolution, signaled the beginning of a transition toward a more open and participatory democratic system. However, the central question posed in this study is to what extent the political culture in the Philippines has truly undergone substantial change following this transition. This study employs a qualitative approach using the literature review method to analyze and examine various secondary sources such as books, academic journals, research institute reports, mass media, and official government documents, as well as to identify the patterns of political culture that have developed from the post-Marcos era to the administration of Ferdinand Marcos Jr. The research analyzes the political dynamics of the Philippines after Marcos, focusing on changes in values, norms, and political practices within both society and the political elite.  The findings show that although the Philippines has made significant progress in institutional aspects—such as relatively free elections, press freedom, and the strengthening of democratic institutions—traditional political culture continues to exert strong influence. This is evident in the persistence of political dynasties, clientelism, and vote-buying practices, particularly in local elections. Despite reforms, political power remains concentrated in elite families, and voter engagement is often shaped more by personal loyalty than by policy orientation.. The study concludes that the transformation of political culture in the Philippines after Marcos has yet to reach the depth necessary to support a mature and sustainable democracy.